Coordinated regulation of IGF1R by HIF1α and HIF2α enhances chemoresistance in glioblastoma - Liao, Bin; Wang, Pan; Gong, Sheng; Zhao, Lu; Liu, Jie; Wu, Nan (Frontiers in Pharmacology, 2025)
BackgroundThis study investigates whether Hypoxia-Inducible Factor 1 alpha (HIF1α) and Hypoxia-Inducible Factor 2 alpha (HIF2α) coordinately regulate insulin-like growth factor 1 receptor (IGF1R) expression, thereby influencing chemosensitivity in glioblastoma multiforme (GBM).MethodsWe analyzed the expression and correlation of HIF1α, HIF2α, and IGF1R in glioma using The Cancer Genome Atlas (TCGA) and Chinese Glioma Genome Atlas (CGGA) databases. Immunohistochemistry (IHC) was performed to detect the expression of HIF1α, HIF2α, and IGF1R in GBM tissues and cells, as well as oxygen tension. Cell cycle analysis, apoptosis assays, lactate dehydrogenase (LDH) release measurements, Western blotting, and xenograft tumor models were employed to explore the synergistic regulation of IGF1R by HIF1α and HIF2α, focusing on activation of the PI3K/AKT signaling pathway and its contribution to GBM drug resistance. Chromatin immunoprecipitation-quantitative PCR (ChIP-qPCR) and dual-luciferase reporter assays were used to investigate the binding sites of HIF1α and HIF2α involved in regulating IGF1R.ResultsOur study demonstrated that HIF1α and HIF2α were highly expressed in GBM tissues and hypoxia-cultured cells, and their expression positively correlated with IGF1R expression. Simultaneous knockout of HIF1α and HIF2α in GBM cells resulted in the highest LDH release and apoptosis rates under hypoxic conditions, accompanied by the most significant decrease in IGF1R, p-PDK1, and p-AKT levels. Knockout of IGF1R in tumor cells under hypoxia led to an increas of LDH release and apoptosis rates, and reduced phosphorylation of PDK1 and AKT. In addition, we demonstrated that HIF1α and HIF2α promoted IGF1R expression by binding to a specific hypoxia response element (HRE) sequence (5′-GAACGTGCCT-3′) within the IGF1R promoter using dual-luciferase reporter system.ConclusionGlioblastoma cells, residing within a hypoxic microenvironment, exhibit high expression of HIF1α and HIF2α. These transcription factors promote the upregulation of IGF1R, which subsequently activates the PI3K/AKT signaling pathway. This activation, in turn, promotes cell proliferation and chemoresistance, ultimately contributing to tumor malignancy.